The scientist and the advertisement: Reklamegutachten in imperial Germany. (December 2020) - Mercelis, Joris
In late nineteenth- and early twentieth-century Germany, the integration of product-evaluating certificates and reports ( Gutachten ) into advertisements triggered repeated condemnations of "advertisement- Gutachten " ( Reklamegutachten ), and scientists and science administrators introduced various restrictions to prevent the appearance of such documents. At the same time, the provision of Gutachten to private individuals and firms seemed crucial to the success of many private and public laboratories. Some chemical and other professionals, moreover, argued that the authoring and use of Reklamegutachten could represent a "scientific" and, therefore, ethical practice. By examining the contested history of the advertisement- Gutachten, this article reveals how a previously tolerated knowledge service lost its legitimacy in a particular place and period of time, and highlights the challenges of eliminating this practice or restoring its legitimacy afterward. The article also explores how professional scientists' approaches to maintaining a reputation for integrity in the face of commercial and competitive pressures related to the better-known efforts of professionals in other fields, particularly the medical. I emphasize that, in determining whether a Gutachten qualified as scientific, the nature and transparency of the underlying research process was only one of the criteria that were considered, and often not the most significant yardstick. At the same time, however, ideas about the personal and professional/institutional integrity of providers of Gutachten were inextricably connected with assessments of the honesty and objectivity of their research.